2021
DOI: 10.3389/fchem.2021.715531
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Doped Luminescent Nanophosphors via Ionic Liquids

Abstract: Lanthanide (Ln3+) ion(s)-doped or rare-earth ion(s)-doped nanomaterials have been considered a very important class of nanophosphors for various photonic and biophotonic applications. Unlike semiconductors and organic-based luminescent particles, the optical properties of Ln3+-doped nanophosphors are independent of the size of the nanoparticles. However, by varying the crystal phase, morphology, and lattice strain of the host materials along with making core-shell structure, the relaxation dynamics of dopant L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 146 publications
0
12
0
Order By: Relevance
“…On the other hand, the cationic part (imidazolium, pyridinium, ammonium, ions, etc.) participates in the capping/templating agent. For example, Zheng et al have shown that the [Emim] + ions can serve as capping agents based on their strong interactions with the (110) facets of rutile, and the [Emim]Br favors the formation of the rutile structure with a rod-like shape due to the mutual π-stacking interactions of imidazole rings . It has been experimentally as well as theoretically proven that the cationic moiety of an IL is self-assembled about the nucleation site during the growth of nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the cationic part (imidazolium, pyridinium, ammonium, ions, etc.) participates in the capping/templating agent. For example, Zheng et al have shown that the [Emim] + ions can serve as capping agents based on their strong interactions with the (110) facets of rutile, and the [Emim]Br favors the formation of the rutile structure with a rod-like shape due to the mutual π-stacking interactions of imidazole rings . It has been experimentally as well as theoretically proven that the cationic moiety of an IL is self-assembled about the nucleation site during the growth of nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, according to the electric dipole selection rule, the 5 D 0 → 7 F 0 transition is only allowed for the following 10 site symmetries, C s , C 1 , C n , and C nv (n = 2, 3, 4, 6) [60,61]. Therefore, the only point groups without an inversion center and showing one band for the 5 D 0 → 7 F 0 transition, two bands for the 5 D 0 → 7 F 1 transition and three bands for the 5 D 0 → 7 F 2 transition are C 3 and C 3v .…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…[6,7,[22][23][24][25] Lately, various GObased nanocomposites materials (NCM) like TiO 2 -graphene nanocomposite, ZnO nanorods/graphene, graphene nanosheet/ Al 2 O 3 , graphene/europium oxide (Eu 2 O 3 ), metal-organic framework (MOFs) composites have been synthesized, which finds huge application in the field of magnetic, lighting, photocatalysis/catalysis, solar cell etc. [7,19,[26][27][28][29][30][31][32] Interestingly, even though the Ln 3 + doped nanoparticles have superior optical and magnetic properties than semiconductor nanocrystals and organic fluorophores, [12][13]15,18,[32][33] the nanocomposite between Ln 3 + doped ions in ternary fluoride with GO as host to offer tunable functionalization capabilities are virtually non-existing. Thus, we undertook this study to describe a successful synthesis of two variants of a nanocomposite between Ln 3 + (Eu or Tb)-doped BaGdF 5 nanoparticles and GO as host material using room temperature, taskspecific ionic liquids based one-pot 'green' synthesis approach.…”
Section: Introductionmentioning
confidence: 99%